(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Acute respiratory tract infections (ARTIs) in children are a common reason for seeking emergency medical care. The severity of these conditions ranges from mild, self-limited illnesses to life-threatening forms of rapidly worsening airway obstruction. A high degree of vigilance is required for prompt diagnosis and initiation of treatment. This review focuses on the general principles of evaluation and management of respiratory emergencies in children, as well as the clinical features and treatment options for specific conditions, including croup, epiglottitis, bacterial tracheitis, retropharyngeal abscess, foreign body ingestion, and toxic inhalation sequelae. Research shows that among the etiological factors of pneumonia, various bacterial and viral agents have been identified, the significance of which is not fully understood, but these cases are characterized by mixed results, lack of complete data and insufficient coverage in the literature. Severe pneumonia is pneumonia characterized by severe respiratory failure (RF) and/or signs of sepsis and multiple organ dysfunction. Today, the problem of severe pneumonia is relevant, due to the high mortality of the disease, the presence of a wide range of poly- and multi- resistant strains of microorganisms. Thus, at present, the study of severe pneumonia in children has not been sufficiently studied, and the issue of using modern methods of preventing infection remains insufficiently addressed. In this regard, issues related to establishing the degree of influence of modifiable and non-modifiable factors on the development and course of severe pneumonia in children require further study; it is necessary to search for new methods for predicting the course and outcome, develop and implement new methods of treatment and prevention of the disease, which determined the relevance of our research. A recirculator is a device for air disinfection. Air from the room enters the recirculator, where it is cleaned, and then it exits back into the room. The air goes in a circle or circulates. Recirculator can be considered any device that starts the process of air circulation, and at the same time cleans it from pollutants, harmful microorganisms. In practice, the word "recirculator" is often used for devices with high efficiency - professional devices or household options with a filtration system that is in no way inferior to medical standards. Usually, these devices are installed in places where there are high requirements and standards for cleanliness. And they reduce the risk of developing dangerous bacterial, viral infections in the room, increase the safety of people and animals that are in it. The device is based on the recirculation of air flows with the effect of ultraviolet radiation with a certain spectrum on the air. If the wavelength is observed within 180-300 nm, then a bactericidal effect on microorganisms will be exerted. As a result, the DNA of the bacterial cell nucleus will be damaged, and then it will be destroyed, the growth and development of pathogenic microorganisms will cease. But to kill viruses, more powerful ultraviolet radiation will be required, its indicator should be within 300-380 nm.